Strategi Pendidikan Karakter Dalam Upaya Membentuk Soft Skill Siswa - Andriani, Wiwin; rofik, Abdur (AL-WIJDÃN Journal of Islamic Education Studies, 2018)
Abstract The discourse of character education’s urgency nowadays, is a response to the issue of apprehensive existence of Indonesian society, which are getting worse in multidimensional crisis. Therefore, the implementation of character education, is rated as the best solution, to overcome the various problems of the nation, through education in schools, especially those which are related with soft skills development of learners as future generation. This qualitative research aims to describe the implementation strategy of character education to soft skills building of learners in school. The data collection technique used is observation’s technique, interview and documentation. Data validity checking done through perseverance observation, Data triangulation, and a detailed description. Data analysis technique used is descriptive componential. The results of this research indicates that 1). The process of character education building is done in two forms of character education curriculum, there are formal education’s curriculum (curriculum of religion’s department) and non-formal education curriculum (curriculum of boarding school/ pesantren); 2). Efforts to implement character education for soft skills building of learners, is done by integrating the values of Aswaja/Nadhlatul Ulama education’s value on all subjects in school.   Keywords: Character education, Soft skills building of learners.